The Effect of Soy Milk with Boiled Moringa Leaves on Blood Sugar Levels in Type 2 Diabetes Mellitus Patients: Study in Bengkulu, Indonesia - Putra, Boy Zedra Ananda Pratama; Maigoda, Tonny Cortis; Desri Suryani (Media Gizi Indonesia, 2024)
Diabetes mellitus is a significant threat to society and even results in death. The content of soybeans that can lower blood glucose levels are protein, isoflavones, fiber, and a low glycemic index. Moringa leaves contain antioxidants such as flavonoids, vitamin A, E, C, and selenium, which help lower blood glucose levels. However, it is unknown whether combining soy milk with boiled moringa leaves is also beneficial in reducing blood sugar levels. This study aimed to determine how combining soy milk and boiled moringa leaves affects blood sugar levels in type 2 diabetes mellitus patients at Posbindu Puskesmas Nusa Indah. Bengkulu city in 2023. The design used in this study is a pre-experimental design with a pre-test and post-test design. Fifteen pre-elderly samples aged 45 to 59 years with blood sugar levels of 140 to 199 mg/dL were randomly selected as intervention targets in this study. The treatment combined 200 ml of soy milk with 150 mL of Moringa leaf decoction, and then 350 mL of soymilk was produced. The intervention was given twice daily, as much as 175 mL for seven days. Data analysis using the Paired T-test showed that there was a significant relationship between intervention and the sugar level of type 2 diabetes mellitus (p < 0.001). There was a substantial decrease in blood glucose levels after administering the soymilk intervention with Moringa leaf decoction after seven days of intervention with p < 0.001. This combination product can be used as a functional food ingredient as an alternative for lowering blood glucose levels.